The Economics of Solidarity: A Conceptual Framework - Alexander S. Kritikos; Friedel Bolle; Jonathan H. W. Tan (European University Viadrina, Department of Business Administration and Economics, 2005)
For many people "solidarity" has become a meaningless word used in slogans - too often used without leading to any economic consequences. We show in this paper conditions under which solidarity can be a powerful instrument. In a solidary action, an individual in a group contributes to a series of actions that aims for a reallocation of scarce resources. The willingness to contribute is mainly influenced by the efficiency of the objective of the solidary action, and is enhanced by feelings of mutual exchange (solidarity) within a group.
Keywords: H40; D71; D60; 330; solidarity; altruism; dynamic; mutual; Solidarität; Altruismus; Gruppentheorie; Nutzenfunktion; Theorie